Early Childhood Education Curriculum Development Policy through Plants Utilization as Nature-Based Learning Media - Nurtina Irsad Rusdiani; Betty Yulia Wulansari; Ardhana Januar Mahardhani (Journal of Science and Education (JSE), 2025)
The implementation of early childhood education curriculum in Indonesia is very diverse. The current curriculum policy only regulates minimum standards that can be developed according to the conditions of the school environment. One of them is the development of a nature-based learning curriculum. This paper aims to explain the use of one of the principles of nature-based learning for early childhood in the early childhood education curriculum, namely learning to utilize nature. One of the media that can be used for learning in nature-based learning is plants. The method of writing this paper is a literature study, namely through books, journals, papers, and the use of social media to obtain valid and accountable data. The results of the discussion of this paper explain how to use roots, stems, twigs, leaves, flowers, and fruits as early childhood learning media in the early childhood learning curriculum. The results of this study can be used by teachers so that learning activities can be more diverse and interesting